A comparative analysis of the main sanctuary interior design of selected evangelical churches - Buyawe, Divine G.
ABSTRACT The study, employing a qualitative research design, aimed at discovering whether or not the selected Evangelical churches have similarities and/or differences in their interior design, and discussing how this may compare to that of Catholic churches. Using a purposeful sampling design, three churches were selected according to their accessibility to the researcher; the United Church of Christ in the Philippines Cosmopolitan, Word of Hope Christian ministries, and the Church of the Risen Lord. In her research framework, the researcher set parameters to include only the main sanctuary of the churches selected, looking into the church beliefs, values, or philosophies, and other non-religious influences that shaped the main sanctuaries' interior design. This became the basis for the design of the study's instrumentations where interviews with the designers of the selected Evangelical churches, observation and photo-documentation of the main sanctuary interiors, and photo-analysis of Catholic Church main sanctuaries were conducted. An inductive study of the gathered data, uncovered the primary factors considered in the design process, and their visible physical translations that revealed the similarities and differences of these churches. After which, a deductive study of the meanings of these findings, applying semiotic analysis as developed by Charles Peirce's, has identified the differences to be primarily on their visual impression as caused by lack of consistency in the use of materials and arrangement of components. The similarities however, lie in their being devoid of ornamentation and non-utilitarian decorations. This phenomenon's resultant idea places "Evangelicalism" as the code operating among the signs and sign-systems observed. Therefore, the churches' unconscious designation of high priority to "evangel" or "gospel", as aligned with their belief, indicate that this could be the reason why there are no strong suggestions of similarities in the interior of the main sanctuaries of the selected Evangelical churches. The researcher recommends further research on this subject to include a wider range of sample, thereby allowing for more developed conclusions on the role of church beliefs, values, and philosophies in shaping the interior design of churches.